A Descriptive Study of Transient Neonatal Feeding Intolerance in a Tertiary Care Center in Turkey. Issue 2 (March 2014) - Cizmeci, Mehmet Nevzat; Kanburoglu, Mehmet Kenan; Akelma, Ahmet Zulfikar; Tufan, Naile; Tatli, Mustafa Mansur
ABSTRACT Objective To investigate the characteristic features of transient neonatal feeding intolerance (TNFI) during the hospitalization for birth in the maternity ward. Design A prospective follow‐up study. Setting Maternity ward and neonatal intensive care unit (NICU) in an academic medical center. Participants Term (≥ 37‐weeks gestation) infants admitted to the neonatal intensive care unit with recurrent vomiting and refusal to feed between January and December 2011. These infants were prospectively followed‐up at 1, 2, 4, 6 months of age in the outpatient clinic. Results During the study period 1280 infants were evaluated in the maternity ward. Forty‐eight (3.75%) neonates with repeated vomiting and refusal to feed were hospitalized from the maternity unit to the NICU Level I on the first postnatal day for further investigation. All infants started vomiting in the first day (median 5.75 hours; interquartile range: 1–24) and recovered by the 48th postnatal hour (median 27.5 hours; interquartile range: 14–48 hours). Laboratory and imaging studies showed no abnormalities. After discharge, 6‐month follow‐up of these infants showed no vomiting or feeding intolerance during well‐child visits. Conclusions Infants with TNFI can be managed with close observation and supportive measures if they have no other indications of underlying disease. We believe that expectant management and supportive measures under skilled nursing care will prevent unnecessary diagnostic evaluation, mother/infant separation, and prolonged hospital stay.